DEDIFFERENTIATED CHORDOMA WITH A SARCOMATOUS COMPONENT: AN OVERLOOKED DIAGNOSIS - Masood, Quratulain; Bilal, Mohammad; Tariq, Ayesha; Khan, Somal; Qureshi, Asad (Journal of Ayub Medical College Abbottabad, 2009)
A 60 year old male presented with unremitting complaints of acute urinary retention and constipation. Computerized Tomography of the abdomen and pelvis confirmed a sacral mass. The biopsy diagnosed dedifferentiated sacral chordoma; an extremely rare entity, seldom reported and frequently misdiagnosed. We present a unique case report after an extensive review of retrospective literature on dedifferentiated chordomas. Keywords: Chordomas, Dedifferentiated chordomas, Sacral chordomas, Malignant fibrous histiocytoma